PENYELESAIAN SENGKETA TERHADAP PERSELISIHAN PERJANJIAN PEMEGANG SAHAM PERSEROAN TERBATAS DI TINJAU DARI PERSPEKTIF ASAS KEPASTIAN HUKUM - Jemy Ronald Vito; Wira Franciska; Gatut Hendrotriwidodo (CORPUS JURIS : JURNAL ILMU HUKUM, 2025)
In this study, the object of analysis is disputes arising from Shareholders Agreements in Limited Liability Companies (PT). The legal phenomenon examined concerns why disputes continue to occur despite shareholders being bound by a Shareholders Agreement that should, in principle, be adhered to as law by those who create it. This research aims to analyze the types of disputes that emerge from the implementation of Shareholders Agreements within a company, the dispute resolution mechanisms employed, and the application of the principle of legal certainty in the dispute resolution process. The research method used is normative legal research with a normative juridical approach, conducted through the examination of laws and regulations, literature, expert opinions, and relevant legal concepts. The results of the study indicate that disputes frequently arising from Shareholders Agreements are caused by differences in interpretation of the agreement’s provisions, breaches of contractual terms, divergent interests and business strategies, rights to dividend distribution, and dispute settlement issues. Dispute resolution mechanisms may be pursued through litigation in court or non-litigation methods such as arbitration. The most effective mechanism for realizing the principle of legal certainty is arbitration-such as the Indonesian National Arbitration Board (BANI) and similar institutions-due to its final and binding decisions as well as its ability to ensure confidentiality and maintain good relations among shareholders. From the perspective of the principle of legal certainty, dispute resolution between shareholders should ideally provide protection for the rights of the parties and ensure that the agreement is implemented in accordance with applicable legal provisions